The Effect of Competence and Job Training on the Performance of Crab Meat Agro-industry Employees in West Java - Raniasari Bimanti Esthi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2022)
The demand for world crab meat increases from year to year, but Indonesia can only partially fulfill it due to problems in fulfilling the resulting product quality. The crab meat agro-industry must have human resources with quality and effectiveness to work by international standards to meet export demand. The problem is that not all agro-industry can fulfil this. One way that can be taken to increase competence is through training so that employee performance increases at the same time; this is set as a research objective. The study's results indicate that training significantly improves employee competence and performance, either directly or indirectly, improving performance through increasing competence. The training must be systematic, starting from the materials required, the methods used and the instructors' abilities. Competencies that increase are essential skills, self-concept, experience and knowledge. Employee performance improved in quality, quantity, timeliness, effectiveness, initiative, and independence.